Differences in the presence of allergens among several types of indoor environments - Barbara Brunetto; Bianca Barletta; Sonia Brescianini; Rosalba Masciulli; Luca Perfetti; Gianna Moscato; Liliana Frusteri; Maria Antonietta Schirru; Carlo Pini; Gabriella Di Felice; Patrizia Iacovacci (Istituto Superiore di Sanità, 2009)
Exposure to indoor allergens can occur both at home and in public places such as schools and workplaces. To investigate and compare the presence of indoor allergens in different kind of environments (schools, offices and homes), dust samples were collected from furniture, desks, mattresses and floors with a standardized procedure. Samples were analyzed for Der p 1, Der f 1, Mite group 2 (mites) and Fel d 1(cat) by monoclonal antibody ELISA assay. Mite allergens were detected with low frequencies in schools and workplaces and with high frequency in homes. Fel d 1 was found with high frequency in every examined environment. Homes rather than public places can represent the environment where people can easier incur in mite allergy. All environments could be at risk for cat allergen exposure.